The importance of the aesthetics of movement in female artistic gymnastics - The judges perspective - Lacerda, T.; Corte-Real, A.; Benigno, S. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The aesthetics of movement expresses the relationship between sports body and space and time. In sports such as gymnastics, artistic skating, platform diving or synchronized swimming, the aesthetics of movement stands on a very obvious dimension and athletes and coaches overlook that relationship. But is it sufficiently recognized and appreciated by judges? Can the experts enable us to identify the features of an aesthetic movement? The main goal of this paper was to identify the importance ascribed by judges to the aesthetics of movement in female artistic gymnastics routines. It was also its purpose to highlight the meaning of the aesthetics of movement in this context, mapping the main categories named by the judges. Methods Eleven international Portuguese judges composed the sample. An intensity scale (from 1 to 5) was used to find out the importance of the aesthetics of movement on the final mark given by the judges. Results 76.9% of the judges admitted that this dimension is of "much" (5) or "sufficient importance" (4) to the appreciation and evaluation of the routine (table 1). The results enhanced also that elegance, grace, harmony, expression, sensibility and souplesse were the most valuable aesthetic categories attached to the aesthetics of movement (table 2). Discussion/Conclusion Witt (1989), Hyland (1990) and Cordner (1995) are some authors that emphasize the existence of an aesthetic performance in gymnastics. Boxill (1988) states that technical efficiency in gymnastics is inseparable from the aesthetics of the performance. The results of our study pointed out in the same direction. In conclusion we may assert that the aesthetics of movement in gymnastics has a great deal of importance on the final mark, what means that the aesthetic judgement plays a remarkable role in the definition of the excellency in this sport.